Strategic Constructions of Diversity in Blame Games Surrounding the Overvaal Furore. Issue 1 (2nd January 2019) - Conradie, Marthinus Stander
ABSTRACT: This article critiques the appropriation of diversity in blame games surrounding the Hoërskool Overvaal (Overvaal High School) controversy that seized media attention in January 2018. Relying on discourse analysis, the study builds on previous research into the discursive practices that structure the imputation of blame for social problems emanating from politically controversial events. For sampling, the study draws from a corpus of nineteen journalistic opinion pieces published by online news sites in reaction to conflict at Overvaal. Its examination unravels a particular construction of diversity in blame games around Overvaal by focusing on an exemplar that narrows the value diversity to two dimensions: the non-racialism achieved through cross-racial contact, and linguistic diversity as conducive to long-term advantages in the labour market. To advance these goals, the study theorises blame as a social practice that involves argumentation. Authors make propositions about blame-worthy individuals or groups, prior to substantiating these claims with reasons. Claims and reasons are bridged by underlying modes of reasoning that may involve taken-for-granted assumptions about social values, such as diversity. As one way of addressing the risk that such values can be reduced to floating signifiers, the study critically assesses a prominent pattern in the way diversity is constructed.